Relationship between Knowledge and Attitudes of Young Women in Dealing with Dysmenorrhea at SMA Negeri 12 Medan 2023: Hubungan Pengetahuan dengan Sikap Remaja Putri dalam Menangani Dismenore di SMA Negeri 12 Medan Tahun 2023 - Indra Hizkia P; Lindawati F. Tampubolon; Eva Lolyta Br. Hutahaean (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2024)
Introduction Attitude is defined as a person's mental status, after he sees something mentally (from within) which then leads to the behavior he shows to other people or objects. The meaning of attitude also means that individuals must be able to communicate or manifest feelings, thoughts, and ego as high as low as to other people or objects, through words, gestures or actions (behaviors). Knowledge is the result of knowing, and this occurs after people sense certain objects. Sensing occurs through the five human senses, namely the senses of sight, hearing, smell, taste and touch. This study aims to determine the relationship between knowledge and attitudes of young women in dealing with dysmenorrhea at SMA Negeri 12 Medan 2023. Method This type of research is quantitative using a cross-sectional design with 198 respondents taking samples using simple random sampling. Result The instrument used is a questionnaire. The results show that 76.3% had poor knowledge and 78.3% has a negative attitude. The data analysis used is univariate and bivariate analysis with the chi-square statistic chi test found p-value = 0.001. These results indicate that there is a relationship between knowledge and attitudes of young women in dealing with dysmenorrhea at SMA Negeri 12 Medan. Conclusion It is expected that young women at SMA Negeri 12 Medan will seek more information about knowledge and attitudes in dealing with dysmenorrhea so that they have broader insights and can handle dysmenorrhea well so that young women at SMA Negeri 12 Medan can have a positive attitude in dealing with dysmenorrhea compared to people who who have less knowledge.